Developing DYRK inhibitors derived from the meridianins as a means of increasing levels of NFAT in the nucleus. Issue 11 (1st June 2017) - Shaw, Simon J.; Goff, Dane A.; Lin, Nan; Singh, Rajinder; Li, Wei; McLaughlin, John; Baltgalvis, Kristen A.; Payan, Donald G.; Kinsella, Todd M.
Graphical abstract: Abstract: A structure-activity relationship has been developed around the meridianin scaffold for inhibition of Dyrk1a. The compounds have been focussed on the inhibition of kinase Dyrk1a, as a means to retain the transcription factor NFAT in the nucleus. NFAT is responsible for up-regulation of genes responsible for the induction of a slow, oxidative skeletal muscle phenotype, which may be an effective treatment for diseases where exercise capacity is compromised. The SAR showed that while strong Dyrk1a binding was possible with the meridianin scaffold the compounds have no effect on NFAT localisation, however, by moving from the indole to a 6-azaindole scaffold both potent Dyrk1a binding and increased NFAT residence time in the nucleus were obtained – properties not observed with the reported Dyrk1a inhibitors. One compound was shown to be effective in an ex vivo muscle fiber assay. The increased biological activity is thought to arise from the added interaction between the azaindole nitrogen and the lysine residue in the back pocket.